Difference in Rill Costs With INA-CBGs Rates and Treatment Rationality of Inpatient Asthma Children - Lorensia, Amelia; Jalmav, Marthy Meliana Ariyanti; Amir, Adilah Fatin; Anizzalati, Fida Shafi (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2024)
Asthma in children may affect children's efficiency at school because frequent attacks occur which disrupt children's activities, so that asthma in children is a serious problem that requires appropriate treatment. The aim was to know the difference in real costs and INA-CBGs rates and to analyze Drug-Related Problems (DRP) based on the severity of asthma and the real costs for childhood asthma at Anwar Medika Sidoarjo Hospital. The design of this study was retrospective using patient medical record data collection, for January 2020-December 2022. Data collection containing real cost data and BPJS claim cost data. Analysis of DRP based on PCNE (Pharmaceutical Care Network Europe) includes problems and causes. There were 77 subjects. the real costs for the severity of mild asthma class I, class III, and moderate asthma class II were high when compared with the INA-CBGS rates, while the severity level of severe asthma class III it was found that the real costs were lower than the INA-CBGS rates. There is no difference between total real costs and INA-CBGS rates for asthma cases in BPJS participating children. The average real cost is Rp. 2,557,453 and the average INA-CBGs tariff is Rp. 2,792,873. There was no significant difference between real costs and INA-CBGS rates (P=0.162). All respondents experienced DRP (100%) and the highest incidence of DRP was M3.1 and P1.2 in 44 people (57.14%) with 180 cases (60.82%). In 77 patients with a total number of cases of 296, the real costs were mostly incurred in class III mild asthma patients (58 people), namely DRP type M3.1 with P1.2 with an average cost of Rp. 2,640,221.